Interim three-dimensional printed overlay prosthesis for an adolescent patient with oligodontia - Deepa Mukkai Krishnamurthy; Rajeev Singh; Gaurang Mistry (Wolters Kluwer Medknow Publications, 2021)
Oligodontia is a developmental anomaly which represents the congenital absence of more than six teeth in primary, permanent, or both dentitions and may or may not be associated with a syndrome. These patients suffer from occlusal disharmony, problems in speech and esthetic appearance. A multidisciplinary approach becomes mandatory to manage such patients to rehabilitate their oral function. Therefore, early diagnosis and treatment become important. This is a case report of a 15-year-old female patient with oligodontia, who was rehabilitated with removable overlay prostheses fabricated digitally, without modifying her existing dentition, to restore mastication, phonetics, and esthetics. Such an approach is essential for children who have not completed their growth. The monolithic three-dimensional (3D) printed denture has increased fracture resistance and higher wear resistance compared to conventional denture. It can also be easily adjusted, repaired and if required, reproduced. This article highlights the methodology, pros and cons of fabricating 3D printed dentures for such patients.